2019
DOI: 10.1002/adhm.201900926
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Trap‐Mimicking DNA‐Histone Mesostructures Synergistically Activate Dendritic Cells

Abstract: Extracellular traps (ETs), such as neutrophil extracellular traps, are a physical mesh deployed by immune cells to entrap and constrain pathogens. ETs are immunogenic structures composed of DNA, histones, and an array of variable protein and peptide components. While much attention has been paid to the multifaceted function of these structures, mechanistic studies of ETs remain challenging due to their heterogeneity and complexity. Here, we report a novel DNA-histone mesostructure (DHM) formed by complexation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…[20] By mimicking the structure, composition, and antimicrobial function of NETs backbone, we have previously reported that DNA-histone μweb suspensions inhibit the proliferation of Gram-negative E. coli in a DNA: histone ratio-dependent manner [19] and that DNA-histone mesostructures (DHMs) stimulate proinflammatory responses from dendritic cells. [21] DHMs form a stable and intact membrane coated on the microwell plates, which can withstand flushing by manual pipetting, as described in Figure 1a. By staining with SYTOX green, the DNA backbone in the DHMs is visualized as a porous mesh (Figure 1b); SEM images (Figure 1c) show that the DNA mesh pore size is approximately 50-300 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] By mimicking the structure, composition, and antimicrobial function of NETs backbone, we have previously reported that DNA-histone μweb suspensions inhibit the proliferation of Gram-negative E. coli in a DNA: histone ratio-dependent manner [19] and that DNA-histone mesostructures (DHMs) stimulate proinflammatory responses from dendritic cells. [21] DHMs form a stable and intact membrane coated on the microwell plates, which can withstand flushing by manual pipetting, as described in Figure 1a. By staining with SYTOX green, the DNA backbone in the DHMs is visualized as a porous mesh (Figure 1b); SEM images (Figure 1c) show that the DNA mesh pore size is approximately 50-300 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of DHMs: To mimic attached NETs, DHMs were prepared by ionic crosslinking of salmon DNA (salmon DNA, Sigma, D1626) using calf thymus histone (Diamond, A002544-0250) in the presence of trehalose dihydrate (Beyotime, ST1245). [21] First, salmon DNA was dissolved into 0.4 m trehalose solution until the final DNA concentration reached 150 μg mL −1 . Next, 40 μL of DNA-trehalose solution was spotted to the center of each well of a 96-well plate (Tissue culture treated, BWTC).…”
Section: Methodsmentioning
confidence: 99%
“…The complexity of the immune system presents many challenges as well as opportunities. Contributions towards these needs can span from innate immune response-mimicking biomaterials 312 that can be easily incorporated into any cell culture to sophisticated long-term OoCs that recreate diseases involving multiple types of immune cell 285 . Overall, OoC models that adequately include human immune systems stand to provide a much needed human-specific context, as the majority of studies are carried out in murine models which often fall short of mimicking human-specific immune physiology.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…As researches showed, NETs increased cytokines and chemokine secretion like IL-6, TNF-α, and GM-CSF which function in DCs maturation [56]. NETs significantly increased surface expression of co-stimulatory molecules (CD40, CD80, CD86) on DCs combined with cytokine secretion of IFN-α, IL-6, and IL-12/p70 and further differentiated CD4 + T cells into various subtypes like Th1 and Th17 cells in cigarette-smoke exposed mice, resulting in airway inflammation and promoting asthma development [20,57]. When DCs were directly stimulated with NETs, the co-stimulatory molecules were elevated, and DCderived IL-6 and TNF-α secretion were enhanced as well.…”
Section: Harmful Functionsmentioning
confidence: 99%